Formulating a Management Maturity Model for Zakat Institutions Using an Organizational Governance Approach - Achmad Zaki; Qurroh Ayuniyyah; Ahmad Juwaini; Hambari; Didin Hafidhuddin (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2026)
This study aims to develop a comprehensive reference framework for assessing the management maturity level of zakat institutions using an organizational governance approach grounded in ISO 37000:2021 (Governance of Organizations) and ISO 37004:2023 (Guidance for Sustainable Governance). Despite zakat’s enormous potential in Indonesia, estimated at IDR 216.54 trillion or 1.75% of GDP, actual collection remains below 10% of this potential. A significant contributing factor is the limited maturity of governance and management practices within zakat institutions. This study employs a sequential mixed-methods design consisting of three integrated stages: a comprehensive desk study and literature review, Focus Group Discussions (FGDs) with 25 practitioners and stakeholders from various LAZ institutions supplemented by semi-structured expert interviews, and the application of the Multi-Stage Weighted Index (MSWI) method. The resulting framework comprises eight governance principles, fifteen dimensions, thirty-four variables, and eighty-three indicators, each evaluated across a six-level maturity scale from Undefined (Level 0) to Optimizing (Level 5). The eight principles, Purpose (21%), Leadership (19%), Risk Governance (13%), Stakeholder Engagement (11%), Accountability (11%), Data and Decision (10%), Viability and Performance Over Time (8%), and Social Responsibility (8%), were weighted through expert consensus. The model produces a composite maturity index scored from 0 to 5, offering broader governance coverage than existing frameworks and providing a standardized, replicable assessment tool applicable across both BAZNAS and LAZ institutions.